Everyday Information Behavior of Marginalized Communities in the Global South: Informal Transportation as Example. Issue 1 (14th October 2022) - Fourie, Ina; Agarwal, Naresh K; Sonnenwald, Diane H; Julien, Heidi; Rorissa, Abebe; Detlor, Brian
Abstract: Information science is increasingly focused on giving voice to marginalized communities, improving their daily lives, and contributing to Sustainable Development Goals (SDGs) and equity, diversity, and inclusion (EDI). However, challenges facing marginalized communities in the Global South are less frequently investigated, yet of great importance. Millions of people depend on information for essential everyday life activities such as transportation. Successful, timely daily commuting between home and work influences financial stability, family time, and safety. Everyday life information behavior as a research lens can reveal information activities, influencing factors, information sources, and contexts applying to informal transportation use by poorer socio‐economic groups. Theories of information behavior such as information poverty and information horizons can shed light. Understanding information behavior contexts, and how to bridge the digital divide and promotion of networking, sharing, and learning for marginalized populations through community‐led digital literacy training can help tailor interventions.